Valuing Rural Meanings: The Work of the Parent Supervisors Challenging Dominant Educational Discourses - Downes, Natalie; Roberts, Philip (Australian and International Journal of Rural Education, 2015)
This paper explores the idea that rurality is important in children's learning even though it is in conflict with dominant educational discourses. Crucial to identifying this was the use of research methods that focused on rural meanings. In this paper we report on an ethnographic study that explored the experiences of parent supervisors of primary school distance education students. The parent supervisors identified that they chose distance education because it enables them to live their rural lifestyle, which in turn reflects the worldview they aim to bring their children up in. However, the schooling they receive values a different, metropolitan-cosmopolitan worldview (Roberts, 2014). In semi-structured interviews parent supervisors described how they would initially focus on conforming to the expectations of schooling, before then realising this was problematic for their students. They would then instead focus on doing what worked for them, which were actions based on their rural ways of being. Ethnography as an approach enabled this research to focus on rural meanings, which identified that parent supervisors work hard to ensure rural perspectives are included when they teach their children because they know this is necessary to meet their children's learning needs. This leads to an important message for school authorities: rurality does matter in education, and education is not confined to the criteria set by school authorities. Importantly, the situated perspective that is implicit in the actions of parent supervisors indicates that adopting a place-conscious (Gruenewald, 2003) approach to schooling would help to sustain rural lifeworlds.